INSIGHTS FROM A 2024 CLINICAL AUDIT OF THYROID STORM CASES AT HOSPITAL SULTAN ISMAIL, JOHOR BAHRU - Kandasamy, Karthik; Lau, Min Yi; Chiew, Ken Seng (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Thyroid storms require immediate medical intervention due to the risk of rapid multi-organ failure and high mortality. Therefore, a retrospective audit of thyroid storm management at Hospital Sultan Ismail, Johor Bahru (HSIJB) was done, to ascertain strengths and identify areas for improvement. METHODOLOGY This audit analyzed all 17 thyroid storm cases admitted to HSIJB in 2024 (1st January 2024 to 31st December 2024). Data was extracted from electronic medical records. RESULT Most were female (70%, n = 12) with mean age of 48 years (range 26 to 75 years). All had Bursch-Wartofsky Point Scale of at least 45 (range 45 to 140). The commonest presentation was cardiovascular manifestations (100% tachycardia, 76% atrial fibrillation, 58% heart failure), followed by gastrointestinal-hepatic dysfunction (53%) and CNS effects (47%). All 5 ventilated patients were co-managed in the ICU. Predominant etiology was Graves’ disease (88%, n = 15), with a case of gestational trophoblastic disease. Main precipitants were medication non-adherence (50%, n = 8), infection (23%, n = 4), and new thyroid diagnosis (29%, n = 5). Treatment was initiated within 6 hours of presentation in 82% of cases (n = 14). In the remaining 3 cases, treatment was delayed by up to 9 hours while awaiting TFT results, as these patients had no prior history of thyrotoxicosis. Aside from one death within 3 days due to thyroid storm and tubo-ovarian abscess, there was no other mortality at up to 180 days after discharge. CONCLUSION Timely intervention in thyroid storms is critical to optimize patient outcomes. However, diagnosis can be challenging, particularly in patients without known thyroid disorders, which may result in delayed treatment. As such, it is essential to initiate therapy promptly based on strong clinical suspicion, even prior to laboratory results. Additionally, addressing issues related to treatment non-adherence through targeted patient education is vital to reduce the incidence of thyroid storm.